The therapeutic potential of vitamins A, C, and D in pancreatic cancer - Alban Piotrowsky; Markus Burkard; Hendrik Schmieder; Sascha Venturelli; Olga Renner; Luigi Marongiu (Heliyon)
The pancreatic ductal adenocarcinoma (PDAC) is among the deadliest tumor diseases worldwide. While treatment options have generally become more diverse, little progress has been made in the treatment of PDAC and the median survival time for patients with locally advanced PDAC is between 8.7 and 13.7 months despite treatment. The aim of this review was to explore the therapeutic potential of complementing standard therapy with natural or synthetic forms of vitamins A, C, and D.The therapeutic use of vitamins A, C, and D could be a promising addition to the treatment of PDAC. For all three vitamins and their derivatives, tumor cell-specific cytotoxicity and growth inhibition against PDAC cells has been demonstrated in vitro and in preclinical animal models. While the antitumor effect of vitamin C is probably mainly due to its pro-oxidative effect in supraphysiological concentrations, vitamin A and vitamin D exert their effect by activating nuclear receptors and influencing gene transcription. In addition, there is increasing evidence that vitamin A and vitamin D influence the tumor stroma, making the tumor tissue more accessible to other therapeutic agents.Based on these promising findings, there is a high urgency to investigate vitamins A, C, and D in a clinical context as a supplement to standard therapy in PDAC. Further studies are needed to better understand the exact mechanism of action of the individual compounds and to develop the best possible treatment regimen. This could contribute to the long-awaited progress in the treatment of this highly lethal tumor entity.